A Study of Video Game Influences on Memory and Attention (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study delves at the ways in which video games impact memory and attention, specifically looking at how gaming can impact cognitive abilities that are crucial for everyday tasks and learning. We can't imagine life without ICTs, or information and communication technologies. Video games and other technological advancements have gained immense popularity among both younger and older generations. Both the video game business and research into how gaming affects people's lives have grown substantially in recent years. This study takes a look at research on the potential benefits of video games for cognitive development, specifically looking at memory & attention training, and particularly at a new approach to teaching VWM using video games. The effects of various video game genres on these cognitive domains and their potential practical implications are investigated in this study by reviewing and analysing current studies.